Manajemen Bencana Banjir di Kelurahan Legok Kecamatan Danau Sipin Kota Jambi - Kadri, Hasyim (Universitas Baiturrahim, 2024)
Initial disaster management requires efforts to empower the community to reduce the negative impacts of disasters. The desire to become a volunteer is still low because they do not have adequate knowledge about being prepared to become a disaster volunteer. The process of considering becoming a volunteer is not easy because it involves a cognitive process in decision making. An individual's readiness to become a disaster volunteer is demonstrated by the knowledge, skills and abilities obtained through the education and learning process. Preparedness in facing floods helps communities form and plan actions that need to be taken when there is a flood. From the survey results, there is a lack of public understanding about flood disaster management, the absence of a Flood Disaster Management Task Force Team and a lack of public understanding about the health impacts of flooding such as diarrhea, dengue fever, skin diseases, leptospirosis and triggering Extraordinary Conditions of diseases. spread in Legok Village, Jambi City. The specific target of this service activity is to involve community organizations/mass organizations, Legok Village, Jambi City. This Disaster Management is expected to: Be able to understand material about education about flood disaster management, the formation of a flood disaster task force team and education about the health impacts of flooding on health such as diarrhea, dengue fever, skin diseases, leptospirosis, ISPA, as well as triggering Extraordinary Circumstances infectious diseases. The activity period is October 2022 to January 2023, the location is RT 08, Legok Village, Jambi City, for 15 people. The results obtained by the community from participating in activities, activity participants were able to understand the material properly, activity participants were able to simulate the material correctly, activity participants were able to answer correctly questions related to material evaluation and the formation of a flood disaster task force team in RT 08, Legok Kota sub-district Jambi